Apabetalone lowers serum alkaline phosphatase and improves cardiovascular risk in patients with cardiovascular disease. (November 2019) - Haarhaus, Mathias; Ray, Kausik K.; Nicholls, Stephen J.; Schwartz, Gregory G.; Kulikowski, Ewelina; Johansson, Jan O.; Sweeney, Michael; Halliday, Christopher; Lebioda, Kenneth; Wong, Norman; Brandenburg, Vincent; Beddhu, Srinivasan; et al.
Abstract: Background and aims: In patients with cardiovascular disease, considerable residual risk remains despite evidence-based secondary prevention measures. Alkaline phosphatase (ALP) has been suggested as a modifiable cardiovascular risk factor. We sought to determine whether cardiovascular risk reduction by the bromodomain and extra-terminal (BET) protein inhibitor apabetalone is associated with the concomitant lowering of serum ALP. Methods: In a post-hoc analysis of 795 patients with established coronary heart disease and statin treatment, who participated in phase 2 placebo-controlled trials of apabetalone, we determined the effect of assigned treatment for up to 24 weeks on the incidence of major adverse cardiovascular events (MACE) and serum ALP. Results: Baseline ALP (median 72 U/L) predicted MACE (death, non-fatal myocardial infarction, coronary revascularization, or hospitalization for cardiovascular causes), independent of high-sensitivity C-reactive protein (hsCRP), sex, age, race, study, cardiovascular risk factors, chronic kidney disease (CKD), liver function markers and treatment allocation (hazard ratio [HR] per standard deviation [SD] 1.6, 95% CI 1.19–2.16, p = 0.002). Mean placebo-corrected decreases in ALP from baseline were 9.2% ( p < 0.001) after 12–14 weeks and 7.7% ( p < 0.001) after 24–26 weeks of apabetalone treatment. In the apabetalone group, a 1-SD reduction in ALP was associated with a HR for MACE of 0.64 (95% CI 0.46–0.90, p = 0.009). Conclusions: Serum ALP predicts residual cardiovascular risk, independent of hsCRP, established cardiovascular risk factors and CKD, in patients with cardiovascular disease on statin treatment. Apabetalone lowers serum ALP, which was associated with a lower risk of cardiovascular events. Whether the beneficial cardiovascular effects of apabetalone are causally related to ALP reduction remains undetermined. Graphical abstract: Image 1 Highlights: Alkaline phosphatase (ALP) predicts residual cardiovascular risk in patients with cardiovascular disease on statin treatment. Apabetalone treatment reduces circulating ALP in a dose-dependent fashion. The reduction of circulating ALP by apabetalone is associated with a reduction in major adverse cardiovascular events (MACE). The association of ALP reduction with MACE is independent of concurrent levels of high-sensitivity C-reactive protein.